Peran Women In Tourism Indonesia Sebagai Aktor Non-Negara Dalam Menguatkan Umkm Perempuan Studi Kasus WTID Entrepreneurship 2024 - Desyanti, Ni Luh Putu Krismery; Sushanti, Sukma (Global Mind, 2024)
In the context of the gender gap in entrepreneurship, women face great challenges in sustaining businesses, especially in the tourism sector. This research aims to analyze the role of Women in Tourism Indonesia (WTID) as a non-state actor in empowering women MSMEs through the WTIDEntrepreneurship 2024 program. A qualitative approach was used with in-depth interviews as the main method. The results show that WTID performs three roles according to Clive Archer's concept as an instrument, arena, and independent actor. As an instrument, WTID provides needs-based training and mentoring to increase women's business capacity. As an arena, WTID creates a collaborative space for participants to share experiences and strengthen networks. As an independent actor, WTID demonstrates self-initiative in driving sustainable social and economic change. The conclusion of this study confirms WTID's contribution in strengthening women's MSMEs despite facing internal and external challenges.